Rancang Bangun Sistem Informasi Keuangan Badan Ta’mirul Masjid Nursalam Bantik Beo Kabupaten Kepulauan Talaud - Juhuria Momodahi; Yudi Klaus Patiro; Eliyah Acantha M Sampetoding; Esther Sanda Manapa (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2021)
The role of computers in data processing to produce an information system is very influential in an organization or institution. The involvement of computer technology tools is very helpful in carrying out data processing activities, especially the making of financial reports at BTM at the Nu Salam Bantik Mosque. In recording the receipt and expenditure of shalawat money, problems often occur such as missing or scattered data, torn, and takes a long time. As a result, financial information becomes inaccurate because it is still done manually without involving computer technology. The research conducted discusses the Making and Development of the Financial Information System for the Ta'mirul Mosque of Nur Saalam Bantik. In designing an application, it is carried out by means of insight techniques, observation and literature study. This study is to create an application for the Development of Financial Information Systems for the Ta'mirul Mosque of Nur Salam Bantik using Microsoft Visual Basic 6.0 (VB). Microsoft Visual Basic apart from being referred to as a programming language (Program Language), Visual Basic is also often referred to as a tool (Tool) to produce windows application programs. In general, there are several benefits that can be obtained from using the Microsoft Visual Basic program itself. Computer at Mosque using OS Windows, So the applications created are programming tools that make it easy to use controls for database design.